Tectonic setting of the Permo-Triassic Chiang Khong volcanic rocks, northern Thailand based on petrochemical characteristics - Panjasawatwong Y. (2014)
The inferred Permo-Triassic Chiang Khong volcanic belt is composed of felsic to mafic volcanic rocks and their pyroclastic equivalents. Almost all the least-altered mafic volcanic rocks are lava flows; a few might have occurred as dykes. These mafic volcanic rocks are non-foliated to weakly foliated, and mostly have porphyritic textures. The phenocrysts/microphenocrysts in porphyritic samples are commonly plagioclase, and may include clinopyroxene, olivine, Fe-Ti oxide, apatite and amphibole. The matrix of lava flows ranges texturally from felty to trachytic but a few samples show felty to ophitic/subophitic, and glassy textures, whereas that of possible dyke samples is holocrystalline. The primary matrix constituents are largely plagioclase and variable proportions of clinopyroxene, Fe-Ti oxide, amphibole, olivine, apatite, quartz, alkali feldspar and/or glass. All the studied samples have been subjected to greenschist-facies regional metamorphism. Chemically, the samples show narrow ranges of least-mobile incompatible-element ratios and range compositionally from dacitc to basalt of tholeiitic series. These samples are chemically analogous to those of the Tertiary andesite from Sardinian Rift, Sardinia, Italy, particularly in terms of least-mobile incompatible-element ratios. Accordingly, the studied mafic volcanic rocks are interpreted to have formed in a continental volcanic arc. However, the problem related to the geometry of plate convergence, giving rise to the continental volcanic arc, still exists.